Goat Annual Reproductive Performance Index (G-ARPI) - CGIAR Research Program on Livestock (2019)
The index has been developed and scores defined for 242 goat flocks in Ethiopia which are linked to CRP interventions allowing to demonstrate the usefulness of the index for the evaluation of livestock interventions. The index can be used by other researchers on request, the respective paper is under review.